Plant compounds that induce polychlorinated biphenyl biodegradation by Arthrobacter sp. strain B1B. - Gilbert, E S (1997)
Plant compounds that induced Arthrobacter sp. strain B1B to cometabolize polychlorinated biphenyls (PCBs) were identified by a screening assay based on the formation of a 4,4'-dichlorobiphenyl ring fission product. A chemical component of spearmint (Mentha spicata), l-carvone, induced Arthrobacter sp. strain B1B to cometabolize Aroclor 1242, resulting in significant degradation of 26 peaks in the mixture, including selected tetra- and pentachlorobiphenyls. Evidence for PCB biodegradation included peak disappearance, formation of a phenylhexdienoate ring fission product, and chlorobenzoate accumulation in the culture supernatant. Carvone was not utilized as a growth substrate and was toxic at concentrations of greater than 500 mg liter-1. Several compounds structurally related to l-carvone, including limonene, p-cymene, and isoprene, also induced cometabolism of PCBs by Arthrobacter sp. strain B1B. A structure-activity analysis showed that chemicals with an unsaturated p-menthane structural motif promoted the strongest cometabolism activity. These data suggest that certain plant-derived terpenoids may be useful for promoting enhanced rates of PCB biodegradation by soil bacteria.